In-hospital mortality following surgical lung biopsy for interstitial lung disease in the USA: 2000-2011 - Hutchinson, John P.; Fogarty, Andrew W.; McKeever, Tricia M.; Hubbard, Richard B. (American Thoracic Society, 2016)
Rationale: Surgical lung biopsy can help to determine a specific diagnosis in interstitial lung disease, but has associated risks. Most currently available mortality data are derived from case series and may not be generalizable to broader populations.